2022
DOI: 10.52808/bmsa.7e6.623.026
|View full text |Cite
|
Sign up to set email alerts
|

Angiostrongylus cantonensis en Achatina fulica en la provincia del Napo, Ecuador y el riesgo incrementado de angiostrongiliasis

Abstract: Introducción: Angiostrongylus cantonensis es reconocido como uno de los principales patógenos causantes de la meningoencefalitis eosinofílica, fue identificado en Ecuador por primera vez en 2008. Métodos: se recolectaron 1476 ejemplares de Achatina fulica con el método de captura por unidad de esfuerzo durante 30 minutos, en 3 cantones de la provincia del Napo, con el fin de establecer la prevalencia de infección por A. cantonensis Resultados: el porcentaje total de caracoles infectados fue de 46,5% (687/1476)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Achatina fulica is widely distributed in Brazil, as well as in other countries, and its presence represents a significant epidemiological risk for the transmission of parasitosis such as EM [5,[48][49][50]. Brockelman et al [45] reported that A. cantonensis larvae (L1 and L2) infecting A. fulica were surrounded by soft tissue composed of fibroblasts, while L3 had a dense tissue wall, similar to the granulomas observed in mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achatina fulica is widely distributed in Brazil, as well as in other countries, and its presence represents a significant epidemiological risk for the transmission of parasitosis such as EM [5,[48][49][50]. Brockelman et al [45] reported that A. cantonensis larvae (L1 and L2) infecting A. fulica were surrounded by soft tissue composed of fibroblasts, while L3 had a dense tissue wall, similar to the granulomas observed in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, we propose that the equilibrium between A. fulica and A. cantonensis larvae hinges on the composition of ES products released by the nematode during its tissue migration up to the establishment of the parasitic site, triggering granuloma formation. Indeed, the formation of granulomas in snails infected with nematodes is associated with an immune defense mechanism and a host reaction against the impacts of infection [33,36,49].…”
Section: Discussionmentioning
confidence: 99%